Altered Neurotransmitter Expression in the Corticothalamocortical Network of an Absence Epilepsy Model with impaired Feedforward Inhibition. (15th July 2021) - Adotevi, Nadia; Su, Aini; Peiris, Danushi; Hassan, Muhammad; Leitch, Beulah
Highlights: Evidence of region-specific changes in GABA expression in the stargazer CTC circuit. Intracellular GABA is reduced at stargazer cortical presynaptic PV + terminals. Total glutamate expression is unaltered in the stargazer CTC circuit. Abstract: The episodes of brief unconsciousness in patients with childhood absence epilepsy are a result of corticothalamocortical circuitry dysfunction. This dysfunction may arise from multifactorial mechanisms in patients from different genetic backgrounds. In previous studies using the epileptic stargazer mutant mouse, which experience frequent absence seizures, we reported a deficit in AMPAR-mediated feed-forward inhibition of parvalbumin-containing (PV + ) interneurons. Currently, in order to determine the downstream effects of this impairment on neurotransmitter expression, we performed HPLC of tissue lysates and post-embedding electron microscopy from the cortical and thalamic regions. We report region-specific alterations in GABA expression, but not of glutamate, and most prominently at PV + synaptic terminals. These results suggest that impaired feed forward inhibition may occur via reduced activation of these interneurons and concomitant decreased GABAergic signaling. Further investigations into GABAergic control of corticothalamocortical network activity could be key in our understanding of absence seizure pathogenesis.